Effects of Permafrost Degradation on Soil Carbon and Nitrogen Cycling in Permafrost Wetlands - Wang, Di; Zang, Shuying; Wang, Lingyan; Ma, Dalong; Li, Miao (Frontiers in Earth Science, 2022)
Climate change is one of the greatest threats to high-latitude permafrost and leads to serious permafrost degradation. However, few attention has been paid to whether peat soil carbon or nitrogen is sensitive to permafrost degradation. This study has selected three typical sample areas (MoHe-continuous permafrost, TaHe-Island-shaped melting permafrost, Jagdaqi-Island-shaped melting permafrost) as research object to compare the response rate and degree of peat soil carbon and nitrogen under permafrost degradation. The results show that soil organic carbon and nitrogen contents are the highest in 0-10 cm soil and permafrost regions show obvious surface aggregation. The carbon content of different types of frozen soil decreases with the depth of soil layer, and the differences are significant (P < 0.01). The distribution pattern of total nitrogen content in each soil layer among different permafrost types is Mohe < Tahe < Jagedaqi. And when it is getting vertically deeper than the surface layer, there is no significant difference between the soil layers in soil profile. The study also focuses on the variations of carbon and nitrogen content in different soil layers of peatland in typical permafrost regions. The results show that soil carbon responds faster to the degradation of frozen soil than soil nitrogen. Moreover, the accumulation degree of soil carbon is also significantly higher than soil nitrogen. Under climate change and for better permafrost conservation, it is necessary to study how the peatland’s soil carbon and the nitrogen are influenced by the permafrost degradation in high latitude.